А Content and forms of tests in mathematics. Requirements for the preparation of pedagogical tests - Адигезалов, Улфат (Pedagogy and Psychology, 2021)
The article highlights important aspects of testing the educational activities of students. In the approach to the test methodology, diametrically opposed views are presented, and the author also expressed his opinion on this matter. The word "test" has been shown to have a broad meaning. However, the article notes that the main object of the research is the term "pedagogical test". The advantages of the test method are listed in order. The difference between the advantages and disadvantages of this method is noted. Among the advantages are the short duration of the test and its coverage of a wide student audience, objectivity, the ability to take into account the individual qualities of students. The article discusses the general requirements for the construction of tests, in connection with which the opinions of methodologists are given and analyzed. Among these examples, the main requirement for test organization was noted - validity. The concept of "validity" is explained. Not all test requirements are equally important - attention was also paid to this issue. The question of the general classification of tests was briefly touched upon. After that, test samples in mathematics were presented. During the presentation of the tests, the main focus was on non-standard tests. In our opinion, it is better to develop students’ creative thinking with the help of non-standard tests. Finally, at the end, a conclusion was made, where a high assessment of educational activity was given using the test method.